Development of SAVI Model Speaking Skills Textbook Introduction to Surabaya Typical Food for BIPA 2 Learners - Artadiyanti, Ni Made Novi; Suyatno; Yuniseffendri (PT Maju Malaqbi Makkarana, 2024)
This research aims to develop a speaking skills textbook based on the Somatic, Auditory, Visual, and Intellectual (SAVI) model with introduction materials for Surabaya typical foods for Indonesian learners for Foreign Speakers (BIPA) level 2. The development of this textbook is based on the needs of learners who need a contextual and interactive learning approach to improve speaking skills in authentic communicative situations. The research method used is the Research and Development (R&D) method with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. The results of the study show that this textbook is effective and interesting for BIPA learners. The validation of material experts and media experts showed the category of